Indonesia's Response to Australia's Wiretapping of Several Important People in Indonesia in 2013 - Muhammad Zakariya Khandalawi; M. Iqbal Maulana; Anisa Sartika Madaniyah; Bagas Wikan T; Diandra Putri Sophianandita (Synergisia, 2024)
The bilateral relationship between Indonesia and Australia has often experienced ups and downs, including a number of conflicts that have strained relations between the two countries, especially during the administration of President Susilo Bambang Yudhoyono. During the era of President Susilo Bambang Yudhoyono, incidents of espionage received significant media attention when Edward Snowden revealed the identities of several Indonesian officials who were the targets of SIGINT wiretapping operations in Asia, especially in Australia. President SBY (Susilo Bambang Yudhoyono) at that time lost his composure after learning that his cellphone was tapped by the Australian Intelligence Agency. The news of the case conducted by the Australian state against several officials in Indonesia raises the question of how Indonesia is responding to the case. There are concerns about Indonesia's basis for handling these cases, given that news of Australia's prosecution of prominent Indonesian figures was reported in 2013 by Susilo Bambang Yudhoyono, the President of the Republic of Indonesia. Indonesia took several steps in response to the wiretapping. Firstly, Indonesia requested official clarification and clarity from Australia, and secondly, the Indonesian government protested by suspending and rethinking a number of bilateral agreements with Australia for a while until there was a clear response and confidence that there would be no wiretapping of state interests. Although Indonesia showed disappointment regarding the wiretapping action carried out by Australia and Indonesia as the party that decided a number of collaborations, Indonesia first contacted Australia after the disclosure of this case